Selective and sensitive portable colorimetric detection of strontium and iodide ions based on G4 DNAzyme/hemin - Chen, Yi-Ting; Chen, Kai-Wei; Li, Shu-Xuan; Liu, Hong-Yu; Xia, Ming; Ni, Fei; Dai, Xiao-Jun; Gu, Ao-Tian; Wang, Peng; Gong, Chun-Hui; Yang, Yi (Microchemical journal, 2024)
[Display omitted] •This multimodal significantly reducing the economic burden.•Low-cost, portable colorimetric sensors exhibit good repeatability, stability, and selectivity.•The sensor displayed a detection limit of 0.11 nM for Sr2+.•The proposed device can be utilized for on-site detection.•The platform realizes the quantification of Sr2+ and I− in actual samples. The radioactive component strontium-90 (90Sr) has attracted considerable attention, but detection remains challenging because there are no specific energy beams to indicate its presence. Due to the short half-life of 131I (8.04 d), the difficulty of detection without nuclear contamination, and the different analysis methods compared to other artificial radionuclides, research on the rapid detection method of 131I in seawater is minimal. In this work, we propose the design of a novel aptamer-based colorimetric sensing system for the visual detection of strontium and iodide ions. This method is based on the ability of hemin to self-assemble with G4 and form a G4/hemin complex with strong peroxidase-like nanozyme activity. At the same time, in the presence of G4/hemin, I− can synergistically catalyze the oxidation of TMB by H2O2, transforming it from colorless to dark blue oxTMB. Under optimal experimental conditions, absorbance was linearly with Sr2+ concentration from 0.8 nM to 7 μM, with a detection limit of 0.11 nM, and absorbance from 0.05 μM to 100 μM with I− concentration. In addition, an integrated portable colorimetric test platform has been developed to realize the on-site portable detection of I−, providing a technical solution for radioactivity detection and analysis, and helping to monitor the migration of radioactive I− and Sr2+ in the environment.